Implementasi Sustainable Streetscape pada Koridor Jalan Jenderal Basuki Rahmat, Kota Malang berdasarkan Persepsi Masyarakat - Fanda, Aigan Mubiena; Ernawati, Jenny; Santoso, Joko Triwinarto (RUAS, 2024)
However, not all cities have uniformly implemented sustainable streetscape, particularly in the context of historic corridors, despite its critical role in enhancing urban success and boosting tourist appeal. The goal of this study is to look at how to create sustainable streetscapes using urban and social principles and public opinion. The Jalan Jenderal Basuki Rahmat corridor after the changes was used as an example. This research utilizes a descriptive quantitative method to identify the actual conditions through direct observations and public impressions, using questionnaires with a Likert scale, which are then analyzed through mean score analysis. The characteristics of this study include legibility, comfort, safety, beauty, liveliness, and healthy urban communities. The study's results show that, in the public's opinion, the implementation of a sustainable streetscape along the Jalan Jenderal Basuki Rahmat corridor meets urban and social principles. The variables of attractiveness and liveliness got the highest mean scores. The Malang City Government anticipates this research to play a significant role in facilitating the city's success.